Immersive Brand Experiences in The Metaverse: A Qualitative Study of Consumer-Brand Interactions in Virtual Space - Komariyatin, Nurul (Generate Digital Publishing, 2025)
Objective: This research aims to explore how elements of immersive brand experiences in the metaverse-including gamification, interactive narrative, social interaction, visual realism, and the use of blockchain technology and NFTs-contribute to emotional engagement, belonging, and consumer loyalty. Research Design & Methods: This study uses an exploratory qualitative approach with in-depth interview techniques with more than 20 participants who actively interact with brands on metaverse platforms such as Roblox, Decentraland, and The Sandbox. Data analysis was conducted through a thematic approach to identify patterns of consumer engagement and perception. Findings: The results show that immersive experiences that are participatory and personalized drive strong emotional attachment to brands. Gamification increases intrinsic motivation, interactive narratives deepen the emotional experience, and social interactions form a sense of community. Realistic visualizations increase trust, while NFT ownership provides a sense of exclusivity and control that strengthens consumer loyalty. Implications & Recommendations: Brands are advised to design holistic metaverse experiences, integrating game elements, stories, communities and blockchain-based digital assets to build more meaningful and sustainable relationships with consumers. Contribution & Value Added: This research makes a theoretical contribution to the study of digital marketing and brand engagement by highlighting the importance of a multidimensional approach based on immersive technology in building consumer loyalty in the Web3 era.